Swine barn dust stimulates CCL9 expression in mouse monocytes through protein kinase C-delta activation - David Schneberger; Jane M Devasure; Kristina L Bailey; Debra J Romberger; Todd A Wyatt (Wolters Kluwer Medknow Publications, 2020)
Objective: Exposure to organic barn dusts has been shown to cause numerous lung problems to chronically exposed animal barn workers. Bacterial components in these dusts trigger innate immunity in the lungs. In characterizing these responses, we examined the expression of a lesser examined chemokine believed to be a lower avidity signal for neutrophil migration, CCL9, and how its expression is controlled by dust exposure in a monocyte/macrophage cell line. Materials and Methods: CCL9 expression was assessed in the RAW267.4 macrophage cell line exposed to organic hog barn dust extracts (HDEs) or components of this dust such as lipopolysaccharide (LPS) and peptidoglycan. CCL9 expression was assessed as well as response of CXCL1 (keratinocyte-derived chemokine [KC]). Protein kinase C (PKC)-α, ζ, and δ were inhibited to assess CCL9 expression. Results: HDE was able to induce significant increase of CCL9 expression in RAW264.7 cells. The ability of HDE to induce CCL9 relied upon LPS present in HDE samples. Addition of CCL9 to RAW264.7 cells stimulated with organic dust reduced KC expression. Further, CCL9 expression was particularly sensitive to PKC-ζ inhibition by chemical or siRNA. Conclusion: CCL9 is an inducible chemokine present in mouse monocytes exposed to HDE. HDE-induced production of CCL9 appears primarily mediated by LPS in HDE samples. This induction appears to require PKC signaling, with emphasis on PKC-ζ expression.